Mechanical strength of lap joints of glass/polyester plates glue with different types of commercial adhesives in the market - Iqbal Mokhtar, 1984-; Yob Saed Ismail, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2010